Integrated drought index for enhanced multi-factor assessment of cropland vulnerability in East Africa - Umugwaneza, Adeline; Chen, Xi; Liu, Tie; Gasirabo, Aboubakar; Umuhoza, Jeanine; Dufatanye Umwali, Edovia; Nyesheja, Enan Muhire; Uwamahoro, Solange; Maniraho, Albert Poponi (Frontiers in Environmental Science, 2025)
East Africa (EA) is becoming more vulnerable to drought, a crisis amplified by climate change, which affects regional livelihoods and food security dependent on rain-fed agriculture. Drought dynamics are not completely understood by current drought assessment methods, as they often neglect to integrate meteorological, agricultural, and hydrological factors. This study addressed this gap by developing the Integrated Drought Index (IDI) using an entropy weighting method. The IDI combines five individual indices and incorporates standardized yield residuals series (SYRS) to capture the multifaceted drought-related impacts on cropland in East Africa from 2001 to 2020. The outcomes revealed overall interannual variations in drought conditions in the study area, with 2005 being particularly severe, affecting 87.3% of the total area. 16.8% and 29.2% experienced extreme and severe drought, respectively. Furthermore, comparisons with standardized drought indices and EM-DAT drought ratios validated the performance of the IDI, demonstrating its high effectiveness in capturing various aspects of drought compared to single-factor indices. SYRS analysis for wheat, dry beans, and maize showed significant yield losses in years of severe drought. With notable yield losses in 2005 and 2008, when drought conditions affected about 87% and 60% of the total area, respectively, maize indicated the highest susceptibility to water stress. These findings highlight the urgent need for adaptive strategies, including drought-tolerant crop varieties, improved water management, and enhanced early warning systems. These are essential to strengthen the resilience of EA to drought, ensuring food security and sustainable livelihoods amidst an increasingly variable climate.